Medical technologists’ experiences handling medical specimens during the COVID-19 pandemic - Mamodiege C. Mafolo; Eunice Mutava; Alethea Sunnasy; Alida S. du Plessis-Faurie (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences)
Background: The severe acute respiratory syndrome coronavirus type 2 virus (SARS-CoV-2) was highly infectious and had a high mortality rate. Globally, countries prioritised early disease detection through biological sample collection, analysis, and treatment. Understanding the physical and mental health outcomes that medical technologists experienced as a result of the increased risk of exposure is critical for making recommendations for the successful implementation of new workplace safety standards.